Avant-Garde Hongroise : 1915-1925. - Éva, Bajkay; De Peuter, Patricia; Petre, Anne; BBL, Brussel; Enikö, Róka (Turnhout : Brepols Publishers, 1999)
Bortnyik, Sandor ; Huszár, Vilmos ; Kassák, Lajos ; Mattis Teutsch, János ; Moholy-Nagy, László ; Nemes Lampérth, József ; Tihanyi, Lajos ; Uitz, Béla ; Peeters, Jozef ; Servranckx, Victor
Avant-Garde Hongroise - Hongaarse Avant-Garde. 1915-1925, BBL, Brussel, 29.10.1999 - 16.01.2000
boek
Keywords: Hongarije